2007
DOI: 10.1162/pres.16.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Soundscapes with Natural Grains

Abstract: We present a technique to facilitate the creation of constantly changing, randomized audio streams from samples of source material. A core motivation is to make it easier to quickly create soundscapes for virtual environments and other scenarios where long streams of audio are used. While mostly in the background, these streams are vital for the creation of mood and realism in these types of applications. Our approach is to extract the component parts of sampled audio signals, and use them to resynthesize a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…No background music is present in the simulation in order to provide as much immersion as possible. By creating a natural, 3D soundscape that the user would expect in this situation, immersion is enhanced (Hoskinson & Pai, 2007;Lumbreras & Ramírez, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…No background music is present in the simulation in order to provide as much immersion as possible. By creating a natural, 3D soundscape that the user would expect in this situation, immersion is enhanced (Hoskinson & Pai, 2007;Lumbreras & Ramírez, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Its interface features knobs and sliders for interactively controlling gain and parameters of multiple samples. To evaluate the platform they conducted an additional study (Hoskinson and Pai 2007) to reveal whether listening subjects found the concatenated sequences convincing compared with genuinely recorded soundscapes.…”
Section: State Of the Art In Concatenative Synthesismentioning
confidence: 99%
“…Hoskinson [8,9] uses a segmentation algorithm based on research in speech-processing and describes grain transitions using a Markov model, while Lu et al [11] and Parker and Behm [15] model and recreate textures by inferring recurrent patterns.…”
Section: Modeling Sound Texturesmentioning
confidence: 99%